2017
DOI: 10.1590/1982-0216201719512216
|View full text |Cite
|
Sign up to set email alerts
|

Otoacoustic emissions in young adults exposed to drums noise of a college band

Abstract: Purpose: to identify cochlear dysfunction and occurrence of tinnitus in young adults exposed to drums noise of a college band.Methods: the sample included 50 subjects: 25 musicians (study group) and 25 non--musicians (control group). The procedures included anamnesis, pure tone audiometry, acoustic impedance and Transient Evoked Otoacoustic Emissions, Distortion Product Otoacoustic Emissions and Distortion Product Otoacoustic Emissions InputOutput function.Results: positive correlation between the occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In the comparison between the frequencies of the DPOAE test, it is noted that the frequency of 5,000 Hz presented diminished amplitude and signal-to-noise ratio -and greater amount of fails -when compared to the other frequencies. Similar datum was found in a study conducted with individuals exposed to drums noise in a college band, which demonstrated, in the frequency of 6,000 Hz in both ears, a tendency of the control group to present better responses than the exposed group 14 . The amplitude of the otoacoustic emissions represents the amount of external hair cells that are sound.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the comparison between the frequencies of the DPOAE test, it is noted that the frequency of 5,000 Hz presented diminished amplitude and signal-to-noise ratio -and greater amount of fails -when compared to the other frequencies. Similar datum was found in a study conducted with individuals exposed to drums noise in a college band, which demonstrated, in the frequency of 6,000 Hz in both ears, a tendency of the control group to present better responses than the exposed group 14 . The amplitude of the otoacoustic emissions represents the amount of external hair cells that are sound.…”
Section: Discussionsupporting
confidence: 87%
“…The results that presented inferior data based on the abovementioned parameters in at least two frequencies were considered altered (with impairment of the external hair cells of the Organ of Corti). The criteria used were developed based on previous studies 13,14 .…”
Section: Criteria For the Analysis Of The Resultsmentioning
confidence: 99%
See 1 more Smart Citation